2019
DOI: 10.1111/beer.12236
|View full text |Cite
|
Sign up to set email alerts
|

“Don't try to teach me, I got nothing to learn”: Management students' perceptions of business ethics teaching

Abstract: Interest is growing towards including business ethics in university curricula, aiming at improving ethical behaviour of future managers. Extant literature has investigated the impact of ethics education on different ethics‐related students' cognitive and/or behavioural outcomes, considering variables related to training programmes and students' demographic aspects. Accordingly, we aim at assessing students' understanding of business ethics issues, by focusing on the differences in students' perceptions dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 111 publications
(206 reference statements)
1
30
0
Order By: Relevance
“…(2018) and Tormo‐Carbó et al. (2019) also find that being female and older predisposes students to increased business ethical sensitivity. Gomes and Graça (2019) factor‐analyze students' CSR‐sensitivity and find that older students value the dimensions of ethics more.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…(2018) and Tormo‐Carbó et al. (2019) also find that being female and older predisposes students to increased business ethical sensitivity. Gomes and Graça (2019) factor‐analyze students' CSR‐sensitivity and find that older students value the dimensions of ethics more.…”
Section: Discussionmentioning
confidence: 93%
“…For this reason, Tormo‐Carbó et al. (2019) also include students' work experience to reflect their levels of exposure and maturity. However, there are situations where years and experiences on campus may validate, or change, students' CSR or ethical disposition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, those university students who show a more positive attitude toward CSR consider that it influences business performance more strongly, which is consistent with the results obtained in previous research works such as those undertaken by Luthar and Karri (2005). Integrating ethical issues and CSR aspects into the curricula could increase the social responsibility and consequences of ethical decisions for society in the future (Tormo‐Carbó, Oltra, Klimkiewicz & Seguí‐Mas, 2019). Our results show that the managers of the future are now receiving education and that critical aspects of social responsibility are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…However, unethical behaviors are still prevalent in the workplace (Weber, 2015). TA B L E 4 Conditional effect of formalism on unethical decision making across different levels of perceptual moral attentiveness Tormo-Carbó, Oltra, Klimkiewicz, and Seguí-Mas (2019) found that students who do not take ethics courses perceive such courses more positively and consider them to be more helpful in solving moral issues at work than those who do take such courses. Therefore, it is suggested that business ethics practitioners pay more attention to course design, content, and implementation in organizations (Tormo-Carbó et al, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%